ANALISIS KELAYAKAN INVESTASI MESIN PENCETAK KEMASAN PADA UD "ROBIN JAYA SENTOSA" SITUBONDO - Nely Supeni; Isti Fadah; Elok Sri Utami (RELASI : JURNAL EKONOMI, 2014)
An investment  is one of alternative policies of the company to develop its business in order to obtain profits in the future. UD "Robin Jaya Sentosa" Situbondo has invested 2 new package printing machines to maximize the company objectives. This study examines whether the proposed investment is worth it or not to do. The data used are primary data and secondary data. Primary data is  investment planning and estimated cash flow. Secondary data is the company's finances. Some investment appraisal methods used are the payback period, average rate of return, net present value, internal rate of return, modified rate of return, profitability index, and monte carlo simulation. The results of analysis shows that the payback period  results is 1 year 10 months 10 days, 101% ARR, NPV of Rp835.044.270, IRR of 68,3%, 45% MIRR, PI of 2,67, and a monte carlo simulation calculations as many as 300 times shows that the probability of NPV<0 by 22%. Based on project acceptance criteria, the results of this analysis indicate that the investment plan of UD "Robin Jaya Sentosa" is feasible.